2008
DOI: 10.1007/s00431-008-0766-2
|View full text |Cite
|
Sign up to set email alerts
|

Practical approach to childhood masturbation—a review

Abstract: The aim of this article is to review the literature for information that could guide the clinical practitioner in the assessment and management of childhood masturbation. The boundary between normal and abnormal or deviant masturbation in children remains unclear. Besides the link with sexual abuse, other environmental factors and individual factors, as well as psychiatric disorders, are mentioned in relation to masturbation and sexual behaviour in general in children. However, evidence-based information is mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 33 publications
1
54
0
3
Order By: Relevance
“…These latter studies underestimate frequencies of childhood sexual behaviors that children intentionally shield from adult view, but nonetheless can offer some useful insights. For example, one study found that masturbation frequencies in the U.S. increased from around 10% by age 7 to around 80% by age 13 (Mallants and Casteels, 2008). As a complement to quantitative studies, ethnographic reports of childhood sociosexuality provide insight into age-, sex-, and context-specific patterns.…”
Section: The Early Development Of Human Sexualitymentioning
confidence: 99%
“…These latter studies underestimate frequencies of childhood sexual behaviors that children intentionally shield from adult view, but nonetheless can offer some useful insights. For example, one study found that masturbation frequencies in the U.S. increased from around 10% by age 7 to around 80% by age 13 (Mallants and Casteels, 2008). As a complement to quantitative studies, ethnographic reports of childhood sociosexuality provide insight into age-, sex-, and context-specific patterns.…”
Section: The Early Development Of Human Sexualitymentioning
confidence: 99%
“…It is recognized that there can be gender differences in the patterns of sexual behavior that are exhibited, though there is little research which describes the differences in the ways in which ISB is demonstrated in males and females. There are some suggestions, for typically developing children, that social and cultural factors and also anatomical differences may lead to referral biases in which males are referred more frequently for treatment than females (Mallants and Casteels 2008;Yang et al 2005). The lack of research in this area makes it very difficult to draw conclusions about any gender differences in terms of the expression of sexual acting out behavior, the severity of ISB, and response to treatment.…”
Section: Discussionmentioning
confidence: 92%
“…In clinical practice, parents of children with disabilities will often voice concern about their child's ISB and may seek advice in this regard (Mallants and Casteels 2008). To date, there is limited research that has investigated different approaches to the treatment of childhood masturbation and even fewer studies that have examined ISB among children with ASD or other types of developmental disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-based information is lacking and, therefore, safety management is advised when a clinician is confronted with childhood masturbation. 2,3 We deduce that normal psychosexual development, as well as environmental and individual factors, should be considered in the assessment and management of childhood masturbation.…”
Section: Introductionmentioning
confidence: 99%